My Reach A Hudson River Memoir - Rogers, Susan Fox (Cornell University Press, 2011)
In this memoir of the Hudson River and of her family, Susan Fox Rogers writes from a fresh perspective: the seat of her kayak. Low in the water, she explores the bays and the larger estuary, riding the tides, marveling over sturgeons and eels, eagles and herons, and spotting the remains of the ice and cement industries. After years of dipping her paddle into the waters off the village of Tivoli, she came to know the rocks and tree limbs, currents and eddies, mansions and islands so well that she claimed that section of the river as her own: her reach. Woven into Rogers's intimate exploration of the river is the story of her life as a woman in the outdoors-rock climbing and hiking as well as kayaking.Rogers writes of the Hudson River with skill and vivacity. Her strong sense of place informs her engagement with a waterway that lured the early Dutch settlers, entranced nineteenth-century painters, and has been marked by decades of pollution. The river and the communities along its banks become partners in Rogers's life and vivid characters in her memoir. Her travels on the river range from short excursions to the Saugerties Lighthouse to a days-long journey from Tivoli to Tarrytown and a circumnavigation of Manhattan Island, while in memory she ventures as far as the Indiana Dunes and the French Pyrenees.In a fluid, engaging voice, My Reach mixes the genres of memoir, outdoor adventure, natural and unnatural history. Rogers's interest in the flora and fauna of the river is as keen as her insight into the people who live and travel along the waterway. She integrates moments of description and environmental context with her own process of grieving the recent deaths of both parents. The result is a book that not only moves the reader but also informs and entertains
Description based on online resource; title from PDF title page (publisher's Web site, viewed Feb. 24, 2017)